Исследование влияния конфигурации магнитной системы сепаратора на постоянных магнитах на распределение магнитного поля в рабочей зоне - Gerlici, J.; Шведчикова, И.А.; Никитченко, И.В; Романченко, Ю.А (Електротехніка і електромеханіка, 2017)
В работе проведено исследование влияния конфигурации магнитной системы (формы и размеров постоянных магнитов) на пространственное распределение индукции магнитного поля в рабочей зоне магнитного сепаратора нового конструктивного исполнения. Поставленные задачи решены с использованием численного метода конечных
элементов. Показано, что кольцевые постоянные магниты с прямоугольной формой поперечного сечения обеспечивают наиболее высокие показатели магнитной индукции в рабочих воздушных зазорах на требуемых расстояниях
от поверхности магнитов. В результате анализа пространственного распределения индукции магнитного поля
установлено, что в межполюсном рабочем объеме сепаратора образуется достаточно интенсивное магнитное
поле с высоким значением градиента индукции. Отмечена целесообразность использования результатов исследования для выбора рациональных конструктивных параметров магнитной системы и определения силовых характеристик сепаратора. У роботі проведено дослідження впливу конфігурації магнітної системи (форми та розмірів постійних магнітів) на
просторовий розподіл індукції магнітного поля в робочій зоні магнітного сепаратора нового конструктивного виконання. Поставлені задачі вирішені з використанням чисельного метода скінченних елементів. Показано, що кільцеві
постійні магніти з прямокутною формою поперечного перетину забезпечують найбільш високі показники магнітної
індукції в робочих повітряних проміжках на необхідних відстанях від поверхні магнітів. За результатами аналізу просторового розподілу індукції магнітного поля встановлено, що в міжполюсному робочому об’ємі сепаратора створюється достатньо інтенсивне магнітне поле з високим значенням градієнта магнітної індукції. Відзначено доцільність
використання результатів досліджень для вибору раціональних конструктивних параметрів магнітної системи та
визначення силових характеристик сепаратора. Purpose. To carry out research the influence of magnetic system
configuration (shape and size of the permanent magnets) on
magnetic field spatial distribution in working area of new structure design magnetic separator with active front surface by numerical methods. Methodology. We have applied the magnetic
field numerical simulation for permanent magnets system in
absence of electrical current in magnetostatic approximation.
We have solved the problem by using finite element method.
Research of permanent magnets cross-sectional shape influence
made in the two-dimensional formulation using software package Elcut. Research of magnetic field induction spatial (threedimensional) distribution in new construction magnetic separator working area is conducted using software package
COMSOL Multiphysics 3.5a. Results. Magnetic flux density
maximum in the immediate vicinity of permanent magnet surface
provide magnets with spherical and trapezoidal cross-sectional
shape. At a distance from pole surface, where the separation
process working, magnetic field density produced by trapezoidal
and spherical cross section magnets, substantially lower in
comparison with rectangular magnets. Rectangular and rectangular with beveled corners cross-section shape magnets create
approximately same magnetic field intensity not significantly
different in weight. Analysis of the spatial distribution of magnetic field induction in the working area of a new construction
magnetic separator has shown that a strong magnetic field with
high magnetic flux density gradient value is formed in the interpolar working volume. Originality. For the first time research of
magnetic flux density distribution in working area of new construction magnetic separator is conducted. Developed device
feature is complex spatial distribution of magnetic field. Practical value. Results of research can be used for selection of rational parameters of separator magnetic system. Received results also can be used for determination of separator force
characteristics.